Audit Of Kediri Sub-District Office Building For Optimizing Electric Energy - Pancane, I Wayan Dikse; Sutama, I Wayan; Ari Gunawan, Made Fandy Santra; Suarjana, I Wayan Gede; Gunardi, Yudhi; Supranartha, Agus (PT. Hafasy Dwi Nawasena, 2024)
An energy audit is a technique used to calculate the amount of energy consumed in buildings and identify ways to reduce it. The Kediri District Office Building currently uses electrical energy efficiently. However, an energy audit is still necessary to determine the amount of electrical energy used, the IKE value, and identify opportunities for energy savings in the Kediri Sub-District Office Building. The data shows that several rooms in the building do not meet the IKE criteria. Out of 13 rooms, 5 are categorized as wasteful, 1 as efficient, 5 as efficient, and 2 as very efficient based on their IKE calculation. To save electrical energy, consider replacing the AC unit and calculating the necessary cooling capacity (PK) for each room based on its area. Additionally, changing the type of load can help meet IKE criteria without compromising the load's function. After implementing the energy-saving method, the Kediri Sub-District Office Building's average monthly electrical energy consumption decreased to 3,233.52, resulting in an annual consumption of 38,802.24. The IKE calculation for each of the 13 rooms showed that 2 rooms were categorized as very efficient, 8 rooms as efficient, and 3 rooms as quite efficient. This resulted in an average energy savings of 746.28 per month and cost savings of Rp. 1,268,325 per month. The English version of the abstract is written using English in the form of past tense and appropriate sentences. Results and conclusions are written in present tense. Abstracts are expected to be more communicative and not monotonous. Text length between 150-250 words. Writing abbreviations and mathematical formulas in the abstract needs to be avoided. The abstract briefly explains the problem, objectives, methods, results and conclusions.